2007
DOI: 10.1016/j.jesp.2006.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cues in social perception: The time course of processing race and facial expression

Abstract: The purpose of the present study was to examine the time course of race and expression processing to determine how these cues influence early perceptual as well as explicit categorization judgments. Despite their importance in social perception, little research has examined how social category information and emotional expression are processed over time. Moreover, although models of face processing suggest that the two cues should be processed independently, this has rarely been directly examined. Event-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
182
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(219 citation statements)
references
References 39 publications
27
182
7
Order By: Relevance
“…Like the P200, this component has also been associated with selective attention (Hillyard & Munte, 1984;Luck & Hillyard, 1994;Ritter et al, 1983;Wijers et al, 1989). Here, White participants have shown greater attention to ingroup White as compared to outgroup Asian and Black faces (Ito et al, 2004;Ito & Urland, 2003Kubota & Ito, 2007;Willadsen-Jensen & Ito, 2006). The different direction of effects in the N200 as compared to the P200 suggests a different psychological mechanism, and consistent with this, N200 amplitude has been associated with depth of processing across several different contexts.…”
Section: P200 and N200supporting
confidence: 68%
See 1 more Smart Citation
“…Like the P200, this component has also been associated with selective attention (Hillyard & Munte, 1984;Luck & Hillyard, 1994;Ritter et al, 1983;Wijers et al, 1989). Here, White participants have shown greater attention to ingroup White as compared to outgroup Asian and Black faces (Ito et al, 2004;Ito & Urland, 2003Kubota & Ito, 2007;Willadsen-Jensen & Ito, 2006). The different direction of effects in the N200 as compared to the P200 suggests a different psychological mechanism, and consistent with this, N200 amplitude has been associated with depth of processing across several different contexts.…”
Section: P200 and N200supporting
confidence: 68%
“…This component has been associated with selective attention, with larger amplitudes associated with greater attention (Hillyard & Munte, 1984;Luck & Hillyard, 1994;Ritter, Simson, & Vaughan, 1983;Wijers, Mulder, Okita, Mulder, & Scheffers, 1989). Studies of race perception have consistently found greater attention by White participants directed to outgroup Asian and Black faces as compared to ingroup White faces (Ito, Thompson, & Cacioppo, 2004;Ito & Urland, 2003Kubota & Ito, 2007;WilladsenJensen & Ito, 2006). Based on the direction of this effect, and on other studies fi nding larger P200s to more negative stimuli (e.g.…”
Section: P200 and N200mentioning
confidence: 99%
“…ERPs derived from EEG have frequently demonstrated the degree to which perceivers automatically attend to (Bradley, 2009) and encode social category information (Ito & Urland, 2003;Kubota & Ito, 2007). A methodological advantage of this approach is high temporal specificity that allows for examination of processes occurring quickly and in succession; in the current experiment, categorization and attention to racial and university membership.…”
Section: Psychophysiological Measuresmentioning
confidence: 88%
“…It is notable that the research showing improved recognition for partialingroup members has used race and university-affiliation as categorical dimensions (Cassidy et al, 2011;Hehman et al, 2010). Previous work has demonstrated the primacy and salience of racial categorization over other possible categorizations (Ito & Urland, 2003;Kubota & Ito, 2007;Willadsen-Jenson & Ito, 2006) and the difficulty in decreasing its salience (Shriver et al, 2008), and we hypothesized that race was a more powerful categorical dimension than universityaffiliation. Therefore, we expected to replicate previous research (Hehman et al, 2010) finding main effects of superior recognition of ingroup members over outgroup members on both racial and university dimensions, but that larger effect sizes would be demonstrated on the racial dimension.…”
Section: Overviewmentioning
confidence: 95%
“…By contrast, the LPP over the frontal-centralparietal area was enlarged by the positive compared to negative affective link priming. As the N2 is larger to one's own face than to others' faces [16] and to famous faces than to unfamiliar ones [17] , the N2 has been associated with individuation and deeper processing of faces [18] . Thus our N2 results suggest that observers may carry out extensive processing or individuation of ethnic in-group faces in terms of affective links between the observer and target faces.…”
Section: Discussionmentioning
confidence: 97%